Hubungan Pemberian ASI Eksklusif dengan Kejadian Penyakit Alergi pada Anak - Annisa Wardhani; Ganung Harsono; . Widardo (Nexus Kedokteran Klinik, 2014)
Background: Allergy defined as hipersensitivity reaction started by immunological mechanism through exposure of allergen to atopic individues. Atopy is genetical tendencies to produce IgE that has been exposed to allergen. Allergic disease that commonly found in children are atopic eczema, asthma bronchial and allergic rhinitis. Whereas food allergy and cows milk allergy are the first allergic disease that could occur for the first time in children. For the past few years, the incidence of allergic disease is increased rapidly, on domestic and global scale. As the result, the prevention of this disease become very important. There are many methods has been done, such as exclusive breatfeeding, avoidance of risk factor and tobacco smoke exposure, and probiotic administration, but the result is remain controversial. This study aims to find out the correlation between exclusive breastfeeding and occurence of allergic disease in children. Methods: This is an analytical survey study using case control approach which was conducted on May-July 2013 in Dr. Moewardi Hospital. The sample was taken using purposive sampling and used rule of thumb to take the amount of sample. Occurence of allergic disease is classified as independent variable and exclusive breastfeeding is classified as dependent variable. The children parents that agree to be taken as a sample signed informed consent and filled the questionnaire. The data about diagnosis was required from medical record. 70 samples of research were obtained and analyzed by using Chi Square test followed by the multivariate logistic regression analysis. Results: Bivariat analysis using Chi Square test showed significant correlation between exclusive breastfeeding with the occurence of allergic disease in children with p<0.05. Exclusive breastfeeding Crude OR was 0.351. By using multivariate logistic regression analysis were obtained adjusted OR = 0.214, p = 0.016 (p<0.05), and 95% CI = 0.061-0.751 for independent variable exclusive breastfeeding. Conclusions: There is a significant correlation between exclusive breastfeeding with the occurence of allergic disease in children (p = 0.016). The OR = 0.214 showed that exclusive breastfeeding is a protective factor against allergic disease in children. Keywords: Exclusive Breastfeeding, Allergic Disease, Atopy